Dynamic Wetting by Nanofluids - Lu, Gui (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2016)
This PhD thesis presents the latest research findings on nanofluid wetting kinetics, which has wide applications in nano/microscale processes and devices. It analyzes complex dynamic wetting by nanofluids using both experiments and multi-scale simulation methods, and presents multiscale (from nano to macroscale) mechanisms and tunable methods to elucidate and control nanofluid dynamic wetting. The book is of interest to university researchers, R&D engineers and graduate students in surface science, materials science and thermal engineering.